Relational Negotiation Processes Between Migrant Care Workers and Mothers: From Caregiving to Fictive Kinship - Canan Neşe Kınıkoğlu; Zehra Zeynep Sadıkoğlu; Fatih Yaman (İstanbul Üniversitesi Sosyoloji Dergisi)
With Türkiye’s adoption of neoliberal policies regarding care services over the last few decades, informally employed migrant care workers have become an important source for providing childcare in Türkiye. This research explores how caregiving roles are negotiated through the relationship between live-in migrant care workers and the mothers who hire them. The study uses a phenomenological approach to focus on five households with migrant care workers in Istanbul, the hub of migrant workers in Türkiye. According to the preliminary findings, a secure relationality between migrant care workers and mothers is established in the first reconciliation phase when the migrant care worker is hired into the household. In the second adaptation phase, cultural similarities and differences between the migrant care worker and the mother arise in the field of childcare. These are negotiated through a fictive kinship, whose borders are often drawn by the mother unilaterally. The last phase consolidates the household routines and orders. Here, the relationality between the migrant care worker and the mother is established through the implicit and open negotiation processes regarding childcare. This research argues that, while this process is predominantly adapted to the expectations of the mother, migrant care workers do not internalize the fictive kinship the mother has constructed and the insecure employment conditions.